Analysis of Political Education Towards Elementary School Learning Process During The Covid-19 - Rani Aprilia; Mariatul Qibtiyah; Kun Budianto; Alva Beriansyah (Political Sciences Program Study, 2024)
This research discusses the analysis of political education towards elementary school learning during the covid-19 pandemic in Palembang City. This research focuses on the political policy of Palembang City education in maintaining education to keep continuing during the covid-19 pandemic. The theory used is the political theory of education by Paulo Freire which is associated with Sarnoto's political concept of education. This theory is used to analyze the political education in Palembang City against the political policy of education during the covid-19 pandemic. The type of research used is descriptive with a qualitative approach. During the covid-19 pandemic, the political role of education is very important in the Palembang City Government because education is the pillar of a country's future. The political role of government education can be seen from the policies made to provide direction. In doing, the education continued operating even in the critical period of education condition during the covid-19 pandemic